2017
DOI: 10.1080/10548408.2016.1245172
|View full text |Cite
|
Sign up to set email alerts
|

Perceived values of TV drama, audience involvement, and behavioral intention in film tourism

Abstract: This study attempts to develop a drama consumption model in the context of film tourism and empirically test it using the mainland Chinese audience of Korean television dramas (K-dramas). Celebrity and dramatized characters strongly influenced the emotional involvement and referential reflection of this audience, whereas the effects of filming location and backdrops were relatively weak in this respect. It is worth noting that the perceived values of K-dramas did not have a direct effect on behavioral intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 38 publications
3
58
2
6
Order By: Relevance
“…One 379 reason for these differences may be that the current study's respondents were Indian expatriates filmed is seen by them as a symbol of prestige. Unlike previous studies where the 398 movie location's scenery, landscape(Kim and Kim, 2018a), cultural and historical attractions, 399 and the local people (Pan and Tsang, 2014) were all motivating factors, the current study's 400 findings revealed that the movie location fulfils numerous motivations of Indian expatriates to…”
contrasting
confidence: 68%
“…One 379 reason for these differences may be that the current study's respondents were Indian expatriates filmed is seen by them as a symbol of prestige. Unlike previous studies where the 398 movie location's scenery, landscape(Kim and Kim, 2018a), cultural and historical attractions, 399 and the local people (Pan and Tsang, 2014) were all motivating factors, the current study's 400 findings revealed that the movie location fulfils numerous motivations of Indian expatriates to…”
contrasting
confidence: 68%
“…It is no surprise that film tourism often incorporates culinary treats. Ranging from the Wallander cake in Ystad, Sweden (Reijnders, 2011: 41), to the New York cupcakes in Sex and the City, and the fried chicken with beer featured in the popular Korean TV drama, My Love from the Star (Kim and Kim, 2018;Tang, 2014), various foods have been made famous by TV and film productions and have subsequently attracted tourists.…”
Section: The Role Of Food In Destination Imagesmentioning
confidence: 99%
“…South Korea stands out as an emerging country in the global geography of creative production of the last two decades, a phenomenon known as Hallyu (literally: Korean wave [ 43 ]). Although Hallyu covers diverse sectors such as music, cinema, food and fashion [ 44 ], TV series (K-dramas) are especially important as they have attracted a global audience [ 45 ], and sparked an unprecedented interest toward Korean culture, and toward Seoul as a global cultural city and destination [ 46 ]. Romantic K-dramas, more specifically, deserve attention as products of a culture that, despite having been historically marked by extreme gender inequality [ 47 ], is now developing new narratives driven by new, vocal female agency [ 48 ], also thanks to the country’s high level of digital literacy that turns online platforms into spaces of co-creation where TV producers can acquire detailed feedback from viewers to take advantage of in future projects.…”
Section: Methods II Romantic K-dramas: a Promising Research Fieldmentioning
confidence: 99%